Au and Co3O4 anchored Bi2WO6 with enhanced electron paramagnetic resonance, surface plasmon resonance, nonlinear and magnetic properties. Issue 7 (6th April 2022) - Chen, Qiuling; Chen, Weihao; Miao, Baoji; Fan, Jianhua
Abstract: The combination of surface plasmon resonance (SPR) effect with hetero‐p–n structure shows promising benefits to optical linear and nonlinear properties. In this study, Au nanoparticles (NPs) decorated p–n hetero‐structured Co3 O4 /Bi2 WO6 composite was synthesized and characterized in terms of the optical linear and nonlinear and magnetic properties, morphology, electron transition, charge transfer, energy band gap, polarizability, SPR effect, and oxygen vacancies using scanning electron microscopy, X‐ray photoelectron spectroscopy, electron paramagnetic resonance spectroscopy, Z‐scan, ultraviolet–visible spectra, and vibrating sample magnetometer. The combination of Co3 O4 provided active 3d electrons transition and charge transfer which increased carriers' concentration and reduced the energy band gap. Au SPR enhanced the internal polarization and strengthened the built‐in electric field, yielding strong nonlinear behavior. In addition, magnetic Co3 O4 endowed sample with room‐temperature ferromagnetism which was obviously strengthened by Au NPs. The obtained sample is promising for laser and photonics applications. Abstract : In this study, we synthesized the Au nanoparticle anchored p–n hetero‐structured Co3 O4 /Bi2 WO6 (BWO) composite. Experiments result revealed that, the Au 3+ was successfully reduced to Au 0 which were well distributed on BWO surface and presented strong SPR peaks. Even though the combination of Co3 O4 and Au did not alter the basic structure and morphology, due to the constructed p–n structure, SPR effect and oxygen vacancy induced by broken of charge balance, the linear and nonlinear optical absorption of sample were greatly enhanced, but energy band gap accordingly was reduced. In addition, the combination of Co3 O4 and Au altered the spin states of Co 2+ ions which greatly increased the magnetization and anisotropy permittivity of sample.